2016
DOI: 10.5604/12321966.1226846
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological characterization of vegetables and their rhizosphere soil in Eastern Poland

Abstract: The aim of this study was to investigate the bacteriological quality of 5 kinds of vegetables (lettuce, dill, radish, beetroot, carrot) and their rhizosphere soil, originating from conventional farms located in the Lublin Province of Eastern Poland. A total number of 35 samples of fresh vegetables (FV) taken immediately from soil, 35 samples of soil from rhizosphere of these vegetables (SR) and 35 samples of vegetables sold at retail in the markets in Lublin (VR) were examined. The samples were analysed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
4
9
0
1
Order By: Relevance
“…The median concentrations of filamentous fungi in examined vegetables were 3.49-5.0 log 10 CFU g -1 , being in the middle of values reported for fungi (moulds and yeasts) determined in the fresh and whole vegetables collected in various countries of the world, which varied within a fairly wide range of 1.1-6.1 log 10 CFU g -1 [2,3,12,13]. Concentrations of filamentous fungi in carrot and beetroot determined in the presented study were similar to the concentrations of aerobic mesophilic bacteria found in these vegetables on conventional farms [14].…”
Section: Levels Of Filamentous Fungi In Root Vegetables and Adjacent supporting
confidence: 72%
“…The median concentrations of filamentous fungi in examined vegetables were 3.49-5.0 log 10 CFU g -1 , being in the middle of values reported for fungi (moulds and yeasts) determined in the fresh and whole vegetables collected in various countries of the world, which varied within a fairly wide range of 1.1-6.1 log 10 CFU g -1 [2,3,12,13]. Concentrations of filamentous fungi in carrot and beetroot determined in the presented study were similar to the concentrations of aerobic mesophilic bacteria found in these vegetables on conventional farms [14].…”
Section: Levels Of Filamentous Fungi In Root Vegetables and Adjacent supporting
confidence: 72%
“…In addition to cooked food, people also eat a lot of raw foods, like vegetables, fruits and berries, which can be contaminated with L monocytogenes , 46 47 E coli , 48–50 Salmonella 49–53 and Campylobacter , 54 and compared with pet food recalls, recalls in human food are much more frequent 55 . Salmonella and Campylobacter can also be isolated from the hands, contact surfaces and cloths in the households where contaminated chicken for human consumption have been handled 56 .…”
Section: Discussionmentioning
confidence: 99%
“…They also found that most of the tested samples of these vegetables contained >5 log 10 cfu g -1 total aerobic bacteria. In the studies by Kłapeć et al [40], the number of mesophilic bacteria in fresh lettuce was 5.27 log 10 cfu g -1 and in dill -4.64 log 10 cfu g -1 . Wójcik-Stopczyńska et al [41] observed that the population of mesophilic bacteria in spinach, immediately after harvesting, ranged from 4.7-5.2 log 10 cfu g -1 .…”
Section: Discussionmentioning
confidence: 91%